The cliometrics of international migration: A survey - Timothy J. Hatton (Institute for the Study of Labor (IZA), 2010)
This is a survey of some of the key studies in the literature on international migration in history that may be described as cliometric. This literature uses the concepts and approaches of applied economics to investigate a range of historical issues and there are strong parallels with the questions that have been addressed in the literature on contemporary migrations. Here I focus on the period 1850 to 1940 and chiefly on migration from Europe to the New World. The survey is organised around six themes that include: the forces driving migration, over time and across space; the assimilation of migrants and their effects on wages and income distribution in source and destination countries; and the evolution of immigration policy. While this literature has drawn heavily on the tool kit of applied economists it also provides a wider perspective on many of the issues that concern migration today.
Keywords: F22; N30; J61; 330; International migration; economic history; Internationale Wanderung; Wirtschaftsgeschichte; Migrationstheorie; Cliometrie; Schätzung; Europäer; Europa; USA